Social Criticism in the Songs of Conflict in Palestine - Nur Hikmah; Hamzah A. Machmoed; Harlinah Sahib (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This research was about the song of conflict in Palestine which aimed to find out social criticism portrayed in the songs of conflict in Palestine, Palestine Will Be Free, Forever Palestine, and We Will not Go Down. This research applied descriptive qualitative method in revealing the data. The research based on the based on Barthes’ theory about semiotics. The findings revealed that there were some social criticisms toward Israel aggression in these songs, such as political, injustice, and religious issue.